Relationship between incidence and prevalence in psychotic disorders: An incidence–prevalence–mortality model. Issue 4 (22nd May 2018) - Pignon, Baptiste; Schürhoff, Franck; Baudin, Grégoire; Tortelli, Andrea; Ferchiou, Aziz; Saba, Ghassen; Richard, Jean‐Romain; Pelissolo, Antoine; Leboyer, Marion; Szöke, Andrei
Abstract: Objectives: Incidence–prevalence–mortality (IPM) models have been developped to estimate incidence or prevalence when one of these two measures is unavailable. We aimed to test the consistency of an IPM model of psychotic disorders on a recent incidence–prevalence couple dataset and to identify potential causes of inconsistency by applying the model to (a) the whole population, (b) female and male subgroups, (c) migrant subgroups, and (d) psychotic disorders with age at onset (AAO) between 18 and 24 (18–24 AAO). Methods: We modelled prevalence (MP) using incidence data and the expected mortality and remission values. We then compared the MP to the observed prevalence (OP). Results: In the whole population, the model significantly underestimated the prevalence (MP = 3.30, 95% CI [2.97, 3.66]; OP = 4.98, 95% CI [4.58, 5.41]). The results were similar for the two genders. In the migrants group, results were in the opposite direction, the model significantly overestimating the prevalence. Finally, in the 18–24 AAO subgroup, the model performed well, with OP and MP not significantly different. Conclusion: These results suggest that standard IPM models do not perform well for psychotic disorders and more complex models taking into account the heterogeneity of the sample (in terms of remission, mortality, population movements, etc.) need to be developed.